Granuloma Mimicking Recurrence of Papillary Thyroid Cancer with Positive FDG-PET SCAN - Nurul Nadia Jamaluddin; Rohaizak M; Nani Harlina ML; Shahrun Niza AS; Suraya A; Yahaya A; Lai YM (Surgical Society of Northern Greece, 2024)
Papillary thyroid cancer (PTC) is the commonest thyroid cancer. It accounts for 85% of thyroid malignancy yet still highly curable. It carries only 5% of disease recurrence with appropriate surgery and nodal dissection. Disease relapse can occur as lymph node metastasis, true soft tissue local recurrence or systemically as a distant metastasis. High resolution neck ultrasound (US) and highly sensitive serum thyroglobulin (Tg) are being used as the standard surveillance tool. There were only a few documented granuloma mimicking recurrences of a well differentiated thyroid cancer in the literature, with positive uptake on FDG PET scan. A 40 year old lady presented with right neck swelling which developed two years after total thyroidectomy and bilateral lymph node dissection for papillary thyroid cancer. She was treated with radioactive iodide ablation once and subsequently showed no uptake on diagnostic WBS. She was asymptomatic throughout surveillance until serum anti thyroglobulin(anti-Tg) was detected to be elevated with normal serum thyroglobulin(Tg). Neck ultrasound identified a lesion at the right thyroid bed with atypical cell seen on ultrasound-guided fine needle aspiration cytology. Whole body scan was negative. Further FDG-PET scan showed positive uptake only in the right thyroid bed. She underwent excision of the lesion using continuous intraoperative nerve monitoring (c- IONM) but complicated with right recurrent laryngeal nerve palsy as detected by reduction of the amplitude. However, histopathology revealed the presence of only granuloma tissue without malignancy cell. Fortunately, her vocal cord function recovers after three months and subsequent serum Tg still normal with persistent slightly elevated anti Tg. Neck ultrasound showed no new lesion detected. Granuloma may mimic the recurrence of papillary thyroid cancer with a positive anti thyroglobulin and false positive FDG-PET scan. The diagnosis of granuloma instead of well differentiated thyroid cancer recurrence might be challenging in the absence of adequate tissue diagnosis. This is important as the need for redo surgery and the risk of unnecessary morbidity is avoidable. It is challenging to differentiate a granuloma from a well differentiated thyroid cancer recurrence in the presence of raised anti Tg and positive PDG-PET scan. Thorough investigation need to be done to avoid unnecessary morbidity of re-do surgery.